(untitled) (Journal of Nepal Geological Society, 1992)
The Lower Tertiary rocks of Nepal Himalaya are classified under the Surkhet Group which comprises Melpani, Swat and Suntar Formations (Paleocene - Lower Miocene). There is perfect stratigraphic harmony between Surkhet Group and underlying Metasediments of Mahabharat Group, Lesser Himalaya (Palaeozoic Mesozoic) with an unconformity. Correlation of the Lower Tertiary rocks of Nepal, India, Pakistan, and their European and North American equivalent is tabulated (Table 2).